2022
DOI: 10.53730/ijhs.v6ns3.8730
|View full text |Cite
|
Sign up to set email alerts
|

Molecular study of quorum sensing and biofilm formation genes in pseudomonas aeruginosa isolated from UTIs patients

Abstract: Background: Urinary tract infection (UTI) is a common health problem in both community and nosocomial settings, affecting both men and women equally. Pseudomonas aeruginosa is an opportunistic human pathogen causing devastating acute and chronic infections in individuals with compromised immune systems. Biofilm is an architecture built mostly by autogenic extracellular polymeric substances which function as a scaffold to encase the bacteria together on surfaces, and to protect them from environmental stresses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…shown Figure (2,3). Biofilm formation was studied [30] on local isolates of P. aeruginosa and found that 45% were strongly biofilm-forming, 48% moderate, and 6.25% were non-biofilm-producing which agreed with current study. However, the percentages obtained in this study differ from [34] which was 100% strong biofilm-producing isolates.…”
Section: Quantification Of Biofilm Formationsupporting
confidence: 88%
“…shown Figure (2,3). Biofilm formation was studied [30] on local isolates of P. aeruginosa and found that 45% were strongly biofilm-forming, 48% moderate, and 6.25% were non-biofilm-producing which agreed with current study. However, the percentages obtained in this study differ from [34] which was 100% strong biofilm-producing isolates.…”
Section: Quantification Of Biofilm Formationsupporting
confidence: 88%